2012
DOI: 10.1111/j.1399-0004.2012.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

PLP1 duplication at the breakpoint regions of an apparently balanced t(X;22) translocation causes Pelizaeus–Merzbacher disease in a girl

Abstract: PLP1 (proteolipid protein1 gene) mutations cause Pelizaeus-Merzbacher disease (PMD), characterized by hypomyelination of the central nervous system, and affecting almost exclusively males. We report on a girl with classical PMD who carries an apparently balanced translocation t(X;22)(q22;q13). By applying array-based comparative genomic hybridization (a-CGH), we detected duplications at 22q13 and Xq22, encompassing 487-546 kb and 543-611 kb, respectively. The additional copies were mapped by fluorescent in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The majority of the men and more than half of the women with this condition are infertile [Dutta et al, 2012]. Translocations involving chromosome 22 and the X chromosome have been reported in literature, although there has been only one case of a female with a karyotype 46,XY,der(22),t(X;22)(pl1.3;pl1) [Pinto et al, 1989;Baumstark et al, 1996;Fonseca et al, 2013]. This is the first report of a female patient with XY chromosomes and Xp duplication involving the DAX1 gene due to X;22 translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the men and more than half of the women with this condition are infertile [Dutta et al, 2012]. Translocations involving chromosome 22 and the X chromosome have been reported in literature, although there has been only one case of a female with a karyotype 46,XY,der(22),t(X;22)(pl1.3;pl1) [Pinto et al, 1989;Baumstark et al, 1996;Fonseca et al, 2013]. This is the first report of a female patient with XY chromosomes and Xp duplication involving the DAX1 gene due to X;22 translocation.…”
Section: Discussionmentioning
confidence: 99%
“…; Fonseca et al. ). Such chromosomal rearrangements should be investigated by fluorescence in situ hybridization (FISH) method, because otherwise, accurate genetic counseling cannot be provided.…”
Section: Genomic Duplicationsmentioning
confidence: 98%
“…In very rare cases, chromosomal translocations involving the PLP1 region have been identified (Hodes et al 2000;Ida et al 2003;Woodward et al 2003;Fonseca et al 2012). Such chromosomal rearrangements should be investigated by fluorescence in situ hybridization (FISH) method, because otherwise, accurate genetic counseling cannot be provided.…”
Section: Genomic Duplicationsmentioning
confidence: 99%
“…Microarray based studies reported copy number variations (microdeletions or microduplications) at the breakpoint(s) of BCR and at other genomic regions far from the breakpoints [Gribble et al, 2005;De Gregori et al, 2007;Baptista et al, 2008;Schluth-Bolard et al, 2009;Fonseca et al, 2013]. These alterations elucidated the abnormal phenotype in 30-50% of the carriers.…”
mentioning
confidence: 99%